How Do Parents Come to Trust Teachers? An Empirical Analysis Based on the Sources of Trust - XIN Zhiyang; WANG Jinghua (Jiaoshi jiaoyu xuebao, 2025)
The source of trust is the foundation for research on trust issues. To explore the two fundamental questions of "whether and to what extent the elements of trust sources influence parents' trust in teachers" and "how the elements of trust sources influence parents' trust in teachers, " this study adopted a mixed-methods approach combining quantitative and qualitative research. Targeting parents of primary school students in Anhui Province, this research analyzed 1, 091 survey responses to examine whether there is influence and the extent of the influence, supplemented by interviews to investigate how the elements of trust resources influence parents' trust. The research has the following findings. First, teachers' qualities, competence, authority-oriented values, and past performance evaluations have significant influence on parents' trust in teachers, collectively accounting for 64.6% of the variance. Second, trust-building elements operate through cultural and institutional pathways. The decisive role of authority-oriented values and teacher quality in establishing trust reflects cultural influences. In the institutionalist explanatory framework, parents' trust in school performance evaluations and teacher competence emerged as outcomes of institutional mechanisms, interpretable as rational assessments of educational outcomes post-enrollment. Third, the cultural and institutional influences are not isolated but interact dynamically in shaping the establishment and evolution of trust.